Musical Traditional Instrument Maker Enterprises e-Commerce System - Azinuddin, Arif; Zainuri, Mohd (Applied Information Technology And Computer Science, 2024)
In Malaysia, integral to cultural events, traditional musical instruments are meticulously crafted by enterprise owners of the musical traditional instrument maker enterprises. However, their manual order management system, reliant on paper records which hard for enterprise owner find related documents and necessitating physical customer visits the shop. This underscores the necessity for an efficient, digitized solution. The project’s objective is to develop and implement a web-based MusicTIMeS system for enterprises, employing an object-oriented approach. The scope includes enterprise, and customer modules with features such as register, login, manage profile, manage product, manage order, manage payment, manage feedback, and generate report. The project concludes with alpha testing, utilizing an iterative model for efficient execution, ensuring adherence to the plan and maintaining a clear direction. MusicTIMeS streamlines enterprise management, benefiting both enterprise owners and customers by facilitating online orders, inquiries, and providing a transparent and efficient ordering process.